2021
DOI: 10.1021/jacs.1c09508
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cu(100)/Cu(111) Interfaces as Superior Active Sites for CO Dimerization During CO2 Electroreduction

Abstract: The electrosynthesis of valuable multicarbon chemicals using carbon dioxide (CO 2 ) as a feedstock has substantially progressed recently but still faces considerable challenges. A major difficulty lines in the sluggish kinetics of forming carbon−carbon (C−C) bonds, especially in neutral media. We report here that oxide-derived copper crystals enclosed by six {100} and eight {111} facets can reduce CO 2 to multicarbon products with a high Faradaic efficiency of 74.9 ± 1.7% at a commercially relevant current den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
129
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(141 citation statements)
references
References 72 publications
12
129
0
Order By: Relevance
“…As a crucial segment of industrial production, the manufacture of C 2+ products ( e.g. , C 2 H 4 , EtOH, AcOH, and PrOH) plays an important role in economy. Recently, electrochemical CO 2 reduction (ECR) has attracted much attention thanks to its potential application for the production of hydrocarbons and carbon oxygenates, especially C 2+ compounds, and the achievement of carbon neutrality. However, electrochemical production of C 2+ compounds generally suffers from poor stability, product selectivity and efficiency, and the reaction mechanism still remains to be explored . Therefore, the design and preparation of new electrocatalysts for yielding C 2+ products should be regarded as one of the most important challenges for the application of ECR.…”
Section: Introductionmentioning
confidence: 99%
“…As a crucial segment of industrial production, the manufacture of C 2+ products ( e.g. , C 2 H 4 , EtOH, AcOH, and PrOH) plays an important role in economy. Recently, electrochemical CO 2 reduction (ECR) has attracted much attention thanks to its potential application for the production of hydrocarbons and carbon oxygenates, especially C 2+ compounds, and the achievement of carbon neutrality. However, electrochemical production of C 2+ compounds generally suffers from poor stability, product selectivity and efficiency, and the reaction mechanism still remains to be explored . Therefore, the design and preparation of new electrocatalysts for yielding C 2+ products should be regarded as one of the most important challenges for the application of ECR.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the CO dimerization has been suggested as a plausible pathway for C–C bond formation, which was also confirmed by online electrochemical mass spectroscopy or by observing *OCCO intermediates via time-resolved attenuated total reflection-surface enhanced infrared absorption spectroscopy (ATR-SEIRAS) . However, the discussion about other possible pathways is still open. , Recently, density functional theory (DFT) calculations suggested the formation of C–C bonds via an OC–COH coupling pathway is thermodynamically and kinetically more favorable than CO dimerized into OCCO. , When optimizing the Cu–CO interaction on a Au-doped Cu(100) or the CO coverage on Cu(100), the OC–COH coupling can be promoted over the competitive CO dimerization.…”
mentioning
confidence: 96%
“…5a). It can be observed that there are obvious CO* characteristic peak bands in the spectra from −0.4 to −1.2 V ( vs. RHE), and the peak bands located at 2140–2150 cm −1 are attributed to the interface stretching vibrational modes of the adsorption of CO. 50 These results reveal that the surface/interface of Cu/Cu 2 O promotes CO dimerization and C 2 products. Density functional theory (DFT) calculations also better revealed the unique activity and selectivity of the CO 2 RR.…”
Section: Resultsmentioning
confidence: 82%